(untitled) (CAHIERS MAGELLANES-NS, 2024)
There is conflicting evidence about the relationship between diabetes, dyslipidemia, and changes in periodontal health. Periodontitis has been linked to an increased risk of diabetes and cardiovascular illnesses, according to recent studies. The aim of this study was to determine the relationship between periodontal status, lipid profiles and glycemic status in a systemically healthy population. Methods: 339 Systemically healthy patients aged between 18-60 years were recruited for this study. A periodontal examination consisting of plaque and bleeding indices and periodontal charting was done. Blood examination consisting of glycemic and lipid parameters were also conducted for all participants. Based on the latest AAP classification of periodontal diseases and conditions, the participants were grouped as periodontally healthy, gingivitis and periodontitis groups and blood parameters were compared across these 3 groups. The obtained data was entered into Microsoft excel sheet and then analyzed using SPSSV 27 software. Results: The glucose and lipid metabolism indexes and blood inflammatory biomarkers did not show to have any correlation with periodontal disease status across both genders of the population. (P>0.05) although their mean values were higher in the disease groups compared to healthy and the mean HDL levels were higher in the healthy group. Conclusion: Although higher mean values of glucose and lipid parameters were found in periodontally diseased groups, their precise correlation needs to be further explored.